Epigenetic regulation of the respiratory chain by a mitochondrial distress-related redox signal - Baeken, Marius W.; Borlepawar, Ankush; Kötzner, Philipp; Richly, Holger; Behl, Christian; Moosmann, Bernd; Hajieva, Parvana (Frontiers in Cell and Developmental Biology, 2025)
Different signaling pathways connect the mitochondrion with the transcriptional machinery in the nucleus. Redox events are thought to play a substantial role along this axis, however, many open questions about their specificity and mode of action remain. Here, we have employed subtoxic doses of the complex I inhibitor MPP+ in human neuronal LUHMES cells to characterize the contribution of scavengeable redox signals to mito-nuclear communication. MPP+ evoked a broadly targeted transcriptional induction of nuclear-encoded respiratory chain complex (RCC) subunits. Nanomolar doses of phenothiazine (PHT), a mitochondrially active antioxidant, attenuated these transcriptional effects by approximately half, but did not modulate the bioenergetic markers ATP, NAD+, NADH, lactate, or glucose. Transcriptional induction by MPP+ was accompanied by a loss of nuclear 5-methyl-cytosine and an increase in histone H3K14 acetylation, both of which were entirely prevented by PHT. Inhibitor and PHT reversibility experiments suggested that these alterations were mediated by lowered DNMT3B and SIRT1 levels, respectively. Analysis of MPTP-treated mice recapitulated the PHT-reversible induction of histone acetylation and DNMT3B suppression in vivo. Moreover, PHT completely abrogated the statistical significance of the association of MPP+ with the selective induction of mitochondrially imported proteins and RCC subunits. We conclude that the mitochondrion employs a redox signal to announce impending, but not yet acute mitochondrial distress to the nucleus, in order to selectively upregulate mito-metabolic genes via chromatin reorganization. Our results have implications for the interpretation of the observed epigenetic changes in Parkinson’s disease and other neurodegenerative disorders.